From steam to diesel : managerial customs and organizational capabilities in the twentieth-century American locomotive industry - Churella, Albert J., 1964- (Princeton, NJ : Princeton University Press, 1998)
A comparative work of business history and the history of technology, the book is not a complete history of any locomotive builder, nor does it explore the origins of the diesel engine in great detail. What it does is to demonstrate how managers addressed radical shifts in technology and production methods. Churella reveals that managerial culture and corporate organizational routines, more than technological competency per se, allowed some companies to succeed, yet constrained the actions of others. He details the shift from small-batch custom manufacturing techniques in the steam locomotive industry to mass-production methods in the diesel locomotive industry.
He also explains that chance events and fortuitous technological linkages helped to shape competitive patterns in the locomotive industry.
I. Steam vs. Diesel: The Capabilities and Requirements of a Radically New Technology -- II. Internal-Combustion Railcars: Springboard to Participation in the Diesel Locomotive Industry -- III. First-Mover Advantages and the Decentralized Corporation -- IV. ALCo and Baldwin: Established Companies, New Technologies -- V. Policy and Production during World War II -- VI. Postwar Dieselization and Industry Shakeout -- VII. The Era of Oligopoly.
Print version record.
Includes bibliographical references and index.
Revision of the author's thesis (Ph. D.)--Ohio State University, 1994.
eBooks on EBSCOhost
Keywords: Locomotive industry -- United States -- Management -- History -- 20th century; Locomotives -- Industrie -- États-Unis -- Gestion -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Industries -- Service; United States; 1900-1999; Samfundsvidenskab -- Økonomi; History